Руководство по обслуживанию и ремонту автомобилей ВАЗ-2108, ВАЗ-2109 - Илюхин А. В. (Имидж-LTD, 1992)
Экземпляры: (20200221) / Инвентарный номер: 30557 / Цена: 25.00 / Сис.шифр: 39.335 / Авт.знак: Р85 / ББК: 39.335.52